Penguatan Kompetensi Guru BK dalam Penerapan Layanan Konseling Realita untuk Permasalahan Belajar Siswa - Nur Mega Aris Saputra; Henny Indreswari; Lutfi Fauzan; Fitri Wahyuni; Tutik Haryanti; M. Khoirudin Jalil (Yayasan Kawanad, 2026)
This community service activity was designed to strengthen the professional capacity of Guidance and Counseling (BK) teachers in applying the reality counseling approach as a relevant strategy for addressing student learning problems at the junior high school level. The training involved 20 BK teachers who are members of the MGBK SMP in Malang City and was conducted through a blended format combining online and face-to-face sessions. Materials covered an introduction to the fundamentals of reality counseling, analysis of learning problems, application of counseling techniques, and the use of digital media. The results showed a significant increase in the understanding, technical skills, and self-confidence of the BK teachers in delivering more effective counseling services. Furthermore, the program served as a platform for sharing best practices and strengthening collaborative networks among BK practitioners. These findings suggest that reality counseling holds considerable potential as a practical approach to improving the quality of guidance services in schools.